ASSESSMENT OF TEACHING MATERIAL IN MECHANICAL ENGINEERING DRAWINGS - Muh Khumaedi (Universitas Sultan Ageng Tirtayasa, 2019)
This study aims at assessing the various educational materials used in teaching mechanical engineering drawing to students of the Department of Mechanical Engineering Education, Semarang State University, and Vocational High School. Data were obtained from 71 university students, 75 public vocational high school 1 students and 37 students of Texmaco Semarang vocational high school using the questionnaire method. Furthermore, descriptive statistics and one-way analysis of variance tests were used to analyze data. The results of the descriptive analysis show that the materials used in teaching mechanical engineering students are in the “very necessary” category, while that of students of vocational high school is in the “necessary” category. The difference in assessment is evidenced from the results of a one-way analysis of variance test, which found differences in the results of the assessment among university students, students of State Vocational High School 1 and Texmaco Vocational High School Semarang.